Implementasi Metode Perbandingan Eksponensial (MPE) Pada Sistem Pendukung Keputusuan Pemilihan Internet Protocol Camera - Umbar Riyanto; Nurdiana Handayani; Mohammad Imam Shalahudin (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
The development of video surveillance has given rise to various types of surveillance cameras, one of which is the Internet Protocol Camera (IP Camera). The number of IP Camera brands in the market, makes people who want to buy IP Cameras have to find their own information about the specifications and capabilities of the IP Camera to be purchased. It takes time and effort to choose an IP Camera, because you have to learn one by one which IP Camera to buy. This study aims to build a decision support system for choosing an IP Camera with a website-based Exponential Comparison Method (MPE) to make it easier to determine the right IP Camera. MPE can sort the priority of decision alternatives on existing criteria and is able to distinguish the value of each alternative in contrast. Based on the case study, the best alternative is Xiaomi Mi 360 with a value of 386, followed by Yi Home Camera 3 getting a value of 369, Ezviz C6N getting a value of 350, Imilab EC4 getting a value of 343 and Cleverdog Egg Cam getting a value of 110. The results of the MPE calculation generated by the system shows the same value as the manual calculation, then the MPE calculation on the system is declared valid. In addition, the test results with black-box testing show that the system can run well.